Preparation method of attapulgite composite cellulose hydrogel material

By preparing the concave and convex rod-soil composite cellulose hydrogel material, the existing adsorbent recovery and secondary pollution are solved by using multiple freeze-drying method and specific component ratios, and the high-efficiency, stable and reusable heavy metal ion adsorption effect is achieved.

CN119633742APending Publication Date: 2025-03-18CHANGZHOU UNIV

Patent Information

Application Number
CN202411370910.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing adsorbents are difficult to recover and reuse after use, and are prone to secondary pollution of water, and their form limits their application scope.

Method used

Multiple freeze-drying methods are used to prepare the composite cellulose hydrogel material of concave and concave soil composite cellulose hydrogel material with appropriate proportions of acid-modified concave and concave soil, sodium alginate, polyvinyl alcohol and sodium carboxymethylcellulose. This material can be efficiently adsorbed heavy metal ions through two mechanisms: chemical adsorption and physical adsorption, and can be prepared into different shapes for easy recycling and reuse.

Benefits of technology

It improves the adsorption rate and stability of heavy metal ions, realizes the efficient, stable and reusable properties of the material, avoids secondary pollution to water bodies, and expands its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633742A_ABST
    Figure CN119633742A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of metal adsorption material preparation, and particularly relates to a preparation method of an attapulgite composite cellulose hydrogel material, which comprises the following steps: (1) uniformly dispersing acid modified attapulgite in water, then adding sodium alginate and polyvinyl alcohol, heating and stirring; (2) adding sodium carboxymethyl cellulose, and continuously stirring to obtain a mixed solution; and (3) injecting the mixed solution into a mold by using an injector, freeze-thawing, freeze-drying, immersing into a CaCl2 solution, cross-linking, washing for multiple times, and freeze-drying again to obtain the attapulgite composite cellulose hydrogel material. Sodium alginate, polyvinyl alcohol, sodium carboxymethyl cellulose and acid modified attapulgite in a proper proportion are matched with a multiple freeze drying method to construct a three-dimensional structure with multiple chemical adsorption, high specific surface area, long diffusion channel and abundant pores, so that the adsorption efficiency and the adsorption capacity of the composite material are improved, and various application requirements are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal adsorption material preparation, and particularly relates to a method for preparing an attapulgite composite cellulose hydrogel material. Background Art

[0002] The rapid development of global industrialization has led to an increase in industrial wastewater discharge, which has seriously affected water resources and ecological balance. Among them, toxic heavy metal ions are key pollutants. Many targeted methods for removing heavy metals have been developed. Adsorption is a widely used wastewater treatment method. Adsorption-based methods are efficient and cost-effective. However, traditional adsorbents cannot be recycled and reused, and tend to be second-hand pollutants. Therefore, it is necessary to prepare new adsorbent materials for such problems, which have the characteristics of high adsorption rate, reusability, easy degradation and no secondary pollution to the environment.

[0003] Most of the current adsorbents, such as CN202410545425.4, disclose an efficient and economical method for treating heavy metals in water, but they have the following defects: First, powdered adsorbents are difficult to recycle and reuse after use, which not only increases the processing cost, but also wastes resources. Secondly, powdered adsorbents form suspensions in water bodies and are easily diffused with the flow of water, increasing the risk of secondary pollution to water bodies. Powdered adsorbent particles are small and difficult to completely separate from water, and residual adsorbents may have a negative impact on aquatic ecosystems. For example, 202410536617.9 discloses the preparation and application of a KOH-modified biochar / attapulgite composite material. Although the high specific surface area of ​​the material is utilized, it is still difficult to recycle and easily causes secondary pollution. In addition, the powder form limits the morphology of the material, and it is impossible to prepare a specific shape suitable for a variety of heavy metal removal situations, thereby limiting its scope of application.

[0004] In response to the defects existing in the existing water pollution treatment, the existing use process cannot be repeatedly recycled and reused and will cause secondary pollution to the original water body. In order to solve the secondary pollution problem caused by the current common adsorbents, the present invention adopts multiple freeze-drying methods, combined with appropriate proportions of acid-modified attapulgite, sodium alginate, polyvinyl alcohol and sodium carboxymethyl cellulose, to prepare a composite cellulose hydrogel material that can be reused, does not cause secondary pollution to the environment, and has good adsorption performance. Summary of the invention

[0005] In order to solve the above-mentioned problems of the prior art, the present invention provides a preparation of a attapulgite composite cellulose hydrogel material, which greatly improves the adsorption rate and adsorption stability of heavy metals in water. On the basis of improving the adsorption effect, the disadvantage of the previous powdered adsorption material in terms of recycling is improved, and a composite multifunctional application material including but not limited to particles, films, and blocks is prepared.

[0006] The principle of the present invention is that its adsorption mechanism includes chemical adsorption and physical adsorption. Chemical adsorption is carried out through ion exchange, electrostatic interaction, metal complexation and π-π conjugation. - , CO, C-OH / COC functional groups play a key role in the adsorption of heavy metals, fixing heavy metal ions on the surface of the material. Physical adsorption relies on polymer chain entanglement, hydrogen bonding, ionic bonding, hydrophobic interaction and electrostatic attraction to form a large number of microporous structures inside the material to capture heavy metal ions. The hydrogel skeleton contains a variety of hydrophilic groups, provides high porosity and water absorption, and ensures that heavy metal ions are evenly dispersed through a three-dimensional network structure to prevent aggregation and oxidation. The composite material maintains efficient adsorption performance under different environmental conditions, has high biocompatibility, low toxicity and degradability, and is suitable for green environmental protection. The acid-modified attapulgite composite material of the present invention has broad application prospects in the adsorption and removal of heavy metal ions in water.

[0007] The technical solution adopted by the present invention is: after acid treatment of attapulgite, attapulgite material with larger specific surface area is prepared. Acid-modified attapulgite nanoparticles are dispersed in a three-dimensional network structure matrix composed of sodium alginate, polyvinyl alcohol and sodium carboxymethyl cellulose. The attapulgite composite cellulose material is prepared by freeze-thawing, freeze-drying, cross-linking and freeze-drying technology for adsorbing heavy metal ions in water.

[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0009] A method for preparing an attapulgite composite cellulose hydrogel material, the specific steps are as follows:

[0010] (1) taking attapulgite (ATP), adding 1-5 mol / L hydrochloric acid solution in a solid-liquid ratio of 1:4, stirring at 50-90°C for 1 hour, filtering the solution, washing with distilled water until the filtrate is neutral, and drying at 105°C to obtain acid-modified attapulgite (H-ATP);

[0011] (2) Dispersing acid-modified attapulgite (H-ATP) in water, ultrasonicating for 30 min, and stirring at room temperature for 1 h;

[0012] (3) adding sodium alginate (SA) and polyvinyl alcohol (PVA) into water and stirring in a water bath at 80°C for 3-6 hours (preferably 4 hours) to completely dissolve them;

[0013] (4) then adding sodium carboxymethyl cellulose (CMC) and continuing stirring for 5-8 h (including 5 h, 6 h, 7 h, and 8 h) to completely dissolve the CMC to obtain a H-ATP / SA / PVA / CMC mixed solution;

[0014] (5) After cooling to room temperature, the obtained mixed solution was injected into the mold using a syringe;

[0015] (6) placing the mold in a -20°C refrigerator for freezing treatment for 16-20 hours, thawing it at room temperature for 4-8 hours (including 4 hours, 5 hours, 6 hours, 7 hours, and 8 hours), and after 2-3 cycles of freezing and thawing, placing it in a freeze dryer for freeze drying for 24 hours;

[0016] (7) Immerse the freeze-dried product in a CaCl2 solution (3-6wt%, including 3wt%, 4wt%, 5wt%, 6wt%) for cross-linking for 3-12h (including 3h, 6h, 9h, 12h), wash with water 3 times to remove excess calcium ions, and finally freeze-dry again for 24h to obtain a attapulgite composite cellulose hydrogel material.

[0017] Furthermore, the mass ratio of the acid-modified attapulgite, sodium alginate, polyvinyl alcohol and sodium carboxymethyl cellulose is 0.5-1.5:1:0.5-1.5:0.5-1.5.

[0018] Preferably, the mass ratio of the acid-modified attapulgite, sodium alginate, polyvinyl alcohol and sodium carboxymethyl cellulose is 1:1:0.5:0.5-1.5.

[0019] Furthermore, the stirring temperature in step (1) is 50-90°C, including 50°C, 60°C, 70°C, 80°C, and 90°C.

[0020] Preferably, the stirring temperature is 70°C.

[0021] The present invention provides a method for preparing a attapulgite composite cellulose hydrogel material, comprising dispersing acidic attapulgite nanoparticles in a three-dimensional network structure matrix composed of sodium alginate, polyvinyl alcohol and sodium carboxymethyl cellulose, utilizing their respective adsorption characteristics and mechanisms, adjusting the component ratio and structure, and cooperating with multiple freeze-drying methods to ensure comprehensive optimization of the material in terms of mechanics, stability and functionality, and achieving efficient heavy metal ion adsorption. Specifically, the acid-modified attapulgite provides a high specific surface area and a negatively charged surface, and adsorbs heavy metal ions through electrostatic adsorption and ion exchange; sodium alginate and sodium carboxymethyl cellulose form complexes with heavy metal ions through their carboxyl groups to improve adsorption efficiency; polyvinyl alcohol enhances the mechanical strength and adsorption capacity of the composite material through its film-forming properties and hydrogen bonding; multiple freeze-drying methods improve and improve the stability and specific surface area of ​​the composite material, and enrich the microporous structure of the composite material. As a result of such a comprehensive effect, an efficient, stable and reusable heavy metal adsorption material is prepared.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention optimizes the ratio of acid-modified attapulgite, sodium alginate, polyvinyl alcohol and sodium carboxymethyl cellulose, and constructs a multiple chemical adsorption mechanism. The negative charge and ion exchange capacity of the acid-modified attapulgite effectively adsorb heavy metal ions; the carboxyl groups in sodium alginate and sodium carboxymethyl cellulose form stable complexes with heavy metals; and the hydroxyl groups in polyvinyl alcohol bind heavy metals through hydrogen bonds. In addition, the combination forms a three-dimensional structure with a large specific surface area and rich pores, which physically captures heavy metals, prolongs the diffusion path, increases the adsorption area, reduces metal aggregation and oxidation, and thus improves the adsorption efficiency.

[0024] 2. The present invention significantly improves the physical properties, stability and adsorption of attapulgite composite cellulose hydrogel materials through a sandwich freeze-drying process. The first freeze-drying process removes moisture and uniformly shrinks the polymer chains. The subsequent secondary freeze-drying after cross-linking further enhances the stability of the cross-linked network and the strength of the material. Multiple freeze-drying optimizes the uniformity of cross-linking, improves the efficiency of the cross-linking reaction, significantly improves the stability and specific surface area of ​​the microporous structure, enhances the water absorption and sustained release properties of the material, and effectively prevents the thermal motion of the polymer chains at high temperatures.

[0025] 3. The composite material of the present invention can be prepared into different shapes, including but not limited to particles, films, and blocks, which are easy to recycle, simple to operate, and can be reused a great number of times. After being used for 5 times, Cd 2+ The removal rate of Cu 2+ The removal rate of Pb 2+ The removal rate dropped from 92.9% to 84.5%, and the removal rates of the three heavy metals decreased by no more than 20%, which can meet the application needs of removing heavy metal pollution in wastewater and soil.

[0026] 4. The composite material of the present invention has the characteristics of low preparation cost, large specific surface area, recyclability and no secondary pollution to water bodies. The attapulgite composite cellulose hydrogel material has a broad application prospect in the field of water treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The figure is the adsorption effect of the original attapulgite and comparative examples 1-5 on metals;

[0028] Figure 2 The X-ray diffraction diagrams of the original attapulgite and the attapulgite modified by hydrochloric acid solutions of different concentrations;

[0029] Figure 3The scanning electron microscope images of the original attapulgite and the attapulgite modified by 4 mol / L hydrochloric acid solution, (a) is the original attapulgite, (b) is the attapulgite modified by 4 mol / L hydrochloric acid solution;

[0030] Figure 4 The figure is a graph showing the adsorption effect of the composite materials of Comparative Examples 6-10 on metals;

[0031] Figure 5 The diagram is a diagram showing the adsorption effect of the materials of Example 2 and Comparative Examples 11-12 on metals;

[0032] Figure 6 The scanning electron microscope images of the materials of Example 2 and Comparative Examples 11-12, (a) is Example 2, (b) is Comparative Example 11, and (c) is Comparative Example 12;

[0033] Figure 7 It is a diagram showing the adsorption effect of the materials of Comparative Example 8 and Examples 1-3 on metals;

[0034] Figure 8 is the X-ray diffraction pattern of the material of Example 2;

[0035] Fig. 9 5 adsorption-desorption experiments of attapulgite composite cellulose hydrogel material (Example 2);

[0036] Fig.10 This is a flow chart for the preparation of attapulgite composite cellulose hydrogel materials. DETAILED DESCRIPTION

[0037] Embodiment 1:

[0038] (1) Take 10 g of original attapulgite (ATP), add 40 mL of 4 mol / L hydrochloric acid solution in a solid-liquid ratio of 1:4, stir at 70 ° C for 1 hour, filter the solution, wash it with distilled water until the filtrate is neutral, and dry the treated ATP at 105 ° C to obtain acid-modified attapulgite (H-ATP).

[0039] (2) Weigh 0.5 g H-ATP and dissolve it in 80 mL water. Ultrasonicate for 30 min and stir at room temperature for 1 h. Then weigh 1 g sodium alginate (SA, Shanghai test) and 0.5 g polyvinyl alcohol (PVA, Shanghai Lingfeng Chemical Reagent Co., Ltd.) and add them to water. Stir in an 80 °C water bath for 4 h to completely dissolve them. Then add 0.5 g sodium carboxymethyl cellulose (CMC, Shanghai test) and continue stirring for 6 h to completely dissolve them to obtain a H-ATP / SA / PVA / CMC mixed solution.

[0040] (3) After cooling to room temperature, the resulting mixed solution was injected into a 10×10×1 cm 3The resulting product was placed in a square mold, and then frozen in a -20°C refrigerator for 18 hours, thawed at room temperature for 6 hours, and after 2 cycles of freezing and thawing, placed in a freeze dryer for freeze drying for 24 hours. Subsequently, it was immersed in a CaCl2 solution (5wt%) for cross-linking for 6 hours, washed with water 3 times to remove excess calcium ions, and finally freeze dried again for 24 hours. The attapulgite composite cellulose hydrogel material was obtained.

[0041] Embodiment 2:

[0042] (1) Same as Example 1.

[0043] (2) Weigh 1 g H-ATP and dissolve it in 80 mL water. Ultrasonicate for 30 min and stir at room temperature for 1 h. Then weigh 1 g SA and 0.5 g PVA and add them to water. Stir in a water bath at 80 °C for 4 h to completely dissolve them. Then add 0.5 g CMC and continue stirring for 6 h to completely dissolve them to obtain a H-ATP / SA / PVA / CMC mixed solution.

[0044] (3) Same as Example 1.

[0045] Embodiment 3:

[0046] (1) Same as Example 1.

[0047] (2) Weigh 1.5 g H-ATP and dissolve it in 80 mL water. Ultrasonicate for 30 min and stir at room temperature for 1 h. Then weigh 1 g SA and 0.5 g PVA and add them to water. Stir in a water bath at 80 °C for 4 h to completely dissolve them. Then add 0.5 g CMC and continue stirring for 6 h to completely dissolve them to obtain a H-ATP / SA / PVA / CMC mixed solution.

[0048] (3) Same as Example 1.

[0049] Example 4

[0050] (1) Same as Example 1.

[0051] (2) Weigh 1 g H-ATP and dissolve it in 80 mL water. Ultrasonicate for 30 min and stir at room temperature for 1 h. Then weigh 1 g SA and 1 g PVA and add them to water. Stir in a water bath at 80 °C for 4 h to completely dissolve them. Then add 1.5 g CMC and continue stirring for 6 h to completely dissolve them to obtain a H-ATP / SA / PVA / CMC mixed solution.

[0052] (3) Same as Example 1.

[0053] Example 5

[0054] (1) Same as Example 1.

[0055] (2) Weigh 1 g H-ATP and dissolve it in 80 mL water. Ultrasonicate for 30 min and stir at room temperature for 1 h. Then weigh 1 g SA and 1.5 g PVA and add them to water. Stir in a water bath at 80 °C for 4 h to completely dissolve them. Then add 1 g CMC and continue stirring for 6 h to completely dissolve them to obtain a H-ATP / SA / PVA / CMC mixed solution.

[0056] (3) Same as Example 1.

[0057] Comparative Example 1:

[0058] The preparation of acid-modified attapulgite comprises the following steps:

[0059] Take 10g of original attapulgite (ATP), add 40mL of 1mol / L hydrochloric acid solution at a solid-liquid ratio of 1:4, stir at 70℃ for 1h, filter the solution, wash with distilled water until the filtrate is neutral, and dry the treated ATP at 105℃ to obtain H-ATP1.

[0060] Comparative Example 2:

[0061] The preparation of acid-modified attapulgite comprises the following steps:

[0062] Take 10g of original attapulgite (ATP), add 40mL of 2mol / L hydrochloric acid solution at a solid-liquid ratio of 1:4, stir at 70℃ for 1h, filter the solution, wash with distilled water until the filtrate is neutral, and dry the treated ATP at 105℃ to obtain H-ATP2.

[0063] Comparative Example 3:

[0064] The preparation of acid-modified attapulgite comprises the following steps:

[0065] Take 10g of original attapulgite (ATP), add 40mL of 3mol / L hydrochloric acid solution at a solid-liquid ratio of 1:4, stir at 70℃ for 1h, filter the solution, wash with distilled water until the filtrate is neutral, and dry the treated ATP at 105℃ to obtain H-ATP3. ;

[0066] Comparative Example 4:

[0067] The preparation of acid-modified attapulgite comprises the following steps:

[0068] Take 10g of original attapulgite (ATP), add 40mL of 4mol / L hydrochloric acid solution at a solid-liquid ratio of 1:4, stir at 70℃ for 1h, filter the solution, wash with distilled water until the filtrate is neutral, and dry the treated ATP at 105℃ to obtain H-ATP4.

[0069] Comparative Example 5:

[0070] The preparation of acid-modified attapulgite comprises the following steps:

[0071] Take 10g of original attapulgite (ATP), add 40mL of 5mol / L hydrochloric acid solution at a solid-liquid ratio of 1:4, stir at 70℃ for 1h, filter the solution, wash with distilled water until the filtrate is neutral, and dry the treated ATP at 105℃ to obtain H-ATP5.

[0072] Comparative Example 6:

[0073] Preparation of Sodium Alginate / Polyvinyl Alcohol Composite Materials

[0074] Weigh 1 g of SA and 1 g of PVA and dissolve them in 80 mL of water. Stir them in a water bath at 80 °C for 4 h to completely dissolve them to obtain a SA / PVA mixed solution.

[0075] After cooling to room temperature, the mixed solution was injected into a 10×10×1 cm 3 The samples were placed in a square mold, and then frozen in a -20°C refrigerator for 18 h, thawed at room temperature for 6 h, and after 2 cycles of freezing and thawing, placed in a freeze dryer for freeze drying for 24 h. Subsequently, the samples were immersed in 100 mL of CaCl2 solution (5 wt%) for cross-linking for 6 h, washed with water 3 times to remove excess calcium ions, and finally freeze dried again for 24 h to obtain a SA / PVA composite material.

[0076] Comparative Example 7:

[0077] Preparation of Sodium Alginate / Polyvinyl Alcohol Composite Materials

[0078] Weigh 1 g SA and 0.5 g PVA and dissolve them in 80 mL water. Stir them in a water bath at 80 °C for 4 h to completely dissolve them to obtain a SA / PVA mixed solution.

[0079] After cooling to room temperature, the mixed solution was injected into a 10×10×1 cm 3 The samples were placed in a square mold, and then frozen in a -20°C refrigerator for 18 h, thawed at room temperature for 6 h, and after 2 cycles of freezing and thawing, placed in a freeze dryer for freeze drying for 24 h. Subsequently, the samples were immersed in 100 mL of CaCl2 solution (5 wt%) for cross-linking for 6 h, washed with water 3 times to remove excess calcium ions, and finally freeze dried again for 24 h to obtain a SA / PVA composite material.

[0080] Comparative Example 8:

[0081] Preparation of Sodium Alginate / Polyvinyl Alcohol / Sodium Carboxymethyl Cellulose Composite Materials

[0082] Weigh 1 g SA and 0.5 g PVA and dissolve them in 80 mL water. Stir them in a water bath at 80 °C for 4 h to completely dissolve them. Then add 0.5 g CMC and continue stirring for 6 h to completely dissolve them to obtain a SA / PVA / CMC mixed solution.

[0083] After cooling to room temperature, the mixed solution was injected into a 10×10×1 cm 3 The samples were placed in a square mold, and then frozen in a -20°C refrigerator for 18 hours, thawed at room temperature for 6 hours, and after 2 cycles of freezing and thawing, placed in a freeze dryer for freeze drying for 24 hours. Subsequently, the samples were immersed in 100 mL of CaCl2 solution (5 wt%) for cross-linking for 6 hours, washed with water 3 times to remove excess calcium ions, and finally freeze dried again for 24 hours to obtain a SA / PVA / CMC composite material.

[0084] Comparative Example 9:

[0085] Preparation of Sodium Alginate / Polyvinyl Alcohol / Sodium Carboxymethyl Cellulose Composite Materials

[0086] Weigh 1 g SA and 0.5 g PVA and dissolve them in 80 mL water. Stir them in a water bath at 80 °C for 4 h to completely dissolve them. Then add 1 g CMC and continue stirring for 6 h to completely dissolve them to obtain a SA / PVA / CMC mixed solution.

[0087] After cooling to room temperature, the mixed solution was injected into a 10×10×1 cm 3 The samples were placed in a square mold, and then frozen in a -20°C refrigerator for 18 hours, thawed at room temperature for 6 hours, and after 2 cycles of freezing and thawing, placed in a freeze dryer for freeze drying for 24 hours. Subsequently, the samples were immersed in 100 mL of CaCl2 solution (5 wt%) for cross-linking for 6 hours, washed with water 3 times to remove excess calcium ions, and finally freeze dried again for 24 hours to obtain a SA / PVA / CMC composite material.

[0088] Comparative Example 10:

[0089] Preparation of Sodium Alginate / Polyvinyl Alcohol / Sodium Carboxymethyl Cellulose Composite Materials

[0090] Weigh 1g SA and 1g PVA and dissolve them in 80mL water. Stir them in a water bath at 80℃ for 4h to completely dissolve them. Then add 1g CMC and continue stirring for 6h to completely dissolve them to obtain a SA / PVA / CMC mixed solution.

[0091] After cooling to room temperature, the mixed solution was injected into a 10×10×1 cm 3 The samples were placed in a square mold, and then frozen in a -20°C refrigerator for 18 hours, thawed at room temperature for 6 hours, and after 2 cycles of freezing and thawing, placed in a freeze dryer for freeze drying for 24 hours. Subsequently, the samples were immersed in 100 mL of CaCl2 solution (5 wt%) for cross-linking for 6 hours, washed with water 3 times to remove excess calcium ions, and finally freeze dried again for 24 hours to obtain a SA / PVA / CMC composite material.

[0092] Comparative Example 11:

[0093] Take 10g of original attapulgite (ATP), add 40mL of 4mol / L hydrochloric acid solution in a solid-liquid ratio of 1:4, stir at 70℃ for 1h, filter the solution, wash it with distilled water until the filtrate is neutral, and dry the treated ATP at 105℃ to obtain acid-modified attapulgite (H-ATP).

[0094] Weigh 1g H-ATP and dissolve it in 80mL water. Ultrasonicate for 30min and stir at room temperature for 1h. Then weigh 1g SA and 0.5g PVA and add them into water. Stir in a water bath at 80℃ for 4h to completely dissolve them. Then add 0.5g CMC and continue stirring for 6h to completely dissolve them to obtain a H-ATP / SA / PVA / CMC mixed solution.

[0095] After cooling to room temperature, the mixed solution was injected into a 10×10×1 cm 3 The square mold was immersed in a CaCl2 solution (5 wt%) for crosslinking for 6 h, washed with water 3 times to remove excess calcium ions, and then freeze-dried for 24 h to obtain an attapulgite composite cellulose hydrogel material.

[0096] Comparative Example 12:

[0097] Take 10g of original attapulgite (ATP), add 40mL of 4mol / L hydrochloric acid solution in a solid-liquid ratio of 1:4, stir at 70℃ for 1h, filter the solution, wash it with distilled water until the filtrate is neutral, and dry the treated ATP at 105℃ to obtain acid-modified attapulgite (H-ATP).

[0098] Weigh 1g H-ATP and dissolve it in 80mL water. Ultrasonicate for 30min and stir at room temperature for 1h. Then weigh 1g SA and 0.5g PVA and add them into water. Stir in a water bath at 80℃ for 4h to completely dissolve them. Then add 0.5g CMC and continue stirring for 6h to completely dissolve them to obtain a H-ATP / SA / PVA / CMC mixed solution.

[0099] After cooling to room temperature, the mixed solution was injected into a 10×10×1 cm 3 The mixture was placed in a square mold, and then frozen in a -20°C refrigerator for 18 hours, thawed at room temperature for 6 hours, and after 2 cycles of freezing and thawing, placed in a freeze dryer for freeze drying for 24 hours. It was then immersed in a CaCl2 solution (5wt%) for crosslinking for 6 hours and washed with water 3 times to remove excess calcium ions. Excess moisture was then dried in a 30°C oven. The attapulgite composite cellulose hydrogel material was obtained.

[0100] Comparative Example 13

[0101] Take 10g of original attapulgite (ATP), add 40mL of 4mol / L hydrochloric acid solution in a solid-liquid ratio of 1:4, stir at 70℃ for 1h, filter the solution, wash it with distilled water until the filtrate is neutral, and dry the treated ATP at 105℃ to obtain acid-modified attapulgite (H-ATP).

[0102] Weigh 1g H-ATP and dissolve it in 80mL water. Ultrasonicate for 30min and stir at room temperature for 1h. Then weigh 1g SA and 2g PVA and add them into water. Stir in a water bath at 80℃ for 4h to completely dissolve them. Then add 1g CMC and continue stirring for 6h to completely dissolve them to obtain a H-ATP / SA / PVA / CMC mixed solution.

[0103] After cooling to room temperature, the mixed solution was injected into a 10×10×1 cm 3 The resulting product was placed in a square mold, and then frozen in a -20°C refrigerator for 18 hours, thawed at room temperature for 6 hours, and after 2 cycles of freezing and thawing, placed in a freeze dryer for freeze drying for 24 hours. Subsequently, it was immersed in a CaCl2 solution (5wt%) for cross-linking for 6 hours, washed with water 3 times to remove excess calcium ions, and finally freeze dried again for 24 hours. The attapulgite composite cellulose hydrogel material was obtained.

[0104] Verification of the effect of removing copper, cadmium and lead from wastewater

[0105] The specific steps are as follows: 25 mg of the materials prepared in the examples and comparative examples are placed in 25 ml of 100 mg / L Cu 2+ 、Cd 2+ and Pb 2+ The solution was placed in a shaking table at 180 r / min for 12 h and then allowed to stand. The supernatant was passed through a membrane and diluted and then the concentrations of Cu(Ⅱ), Cd(Ⅱ) and Pb(Ⅱ) were determined using flame atomic spectrophotometry (novAA-800).

[0106] 1. The experimental results of the acid-modified attapulgite of Comparative Examples 1-5 for removing copper, cadmium and lead from wastewater are shown in Figure 1 Through experiments and characterization, it was found that 4 mol / L hydrochloric acid modified attapulgite has the best effect.

[0107] 2. The experimental results of using the composite materials of comparative examples 6-10 to remove copper, cadmium and lead from wastewater are shown in Figure 4 Through experiments and characterization, it was found that the best effect was achieved when the ratio of sodium alginate (SA), polyvinyl alcohol (PVA), and sodium carboxymethyl cellulose (CMC) was 2:1:1.

[0108] Table 1 Component ratio of the composite materials of Comparative Examples 6-10

[0109]

[0110] 3. The results of the experiment using the materials of Examples 1-3 and Comparative Example 8 to remove copper, cadmium and lead from wastewater are shown in Figure 7 The experiment showed that the best effect was achieved when the acid-modified attapulgite increased by 1 g, with a Cd removal rate of 77.9%, a Cu removal rate of 85.3%, and a Pb removal rate of 92.9%.

[0111] Table 2 Material composition ratio of Examples 1-3 and Comparative Example 8

[0112]

[0113] 4. The results of the experiment using the materials of Example 2 and Comparative Examples 11-12 to remove copper, cadmium and lead from wastewater are shown in Figure 5 , SEM images of the materials of Example 3 and Comparative Examples 11-12 are shown in Figure 6 Through experiments, it was found that the best effect was achieved by freeze-thaw cycle, freeze-drying, cross-linking and solidification, and then freeze-drying again.

[0114] 5. The materials of Comparative Example 13 and Examples 2, 4, and 5 were used in an experiment to remove cadmium, copper, and lead ions from wastewater. The experiment showed that Example 2 had the highest removal rate. The experimental results are shown in Table 3.

[0115] Table 3 Metal adsorption effects of comparative example 13 and embodiments 2, 4, and 5

[0116]

[0117] 6. The material of Example 2 was subjected to a maximum metal adsorption test. 2+ , Cu 2+ and Pb 2+The initial concentration of the solution increased from 50 mg / L to 1000 mg / L. At pH = 5±0.5, 303.15k, the maximum adsorption capacity of cadmium, copper and lead ions by the attapulgite composite cellulose hydrogel material of Example 2 was 341.23 mg / g, 460.82 mg / g and 509.76 mg / g, respectively. The fitted maximum theoretical adsorption capacity of cadmium, copper and lead ions reached 390.62 mg / g, 523.96 mg / g and 586.53 mg / g, respectively (the adsorption process conforms to the Langmuir model).

[0118] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A method for preparing an attapulgite composite cellulose hydrogel material, characterized in that: The preparation method comprises the following steps: (1) Dispersing acid-modified attapulgite uniformly in water, adding sodium alginate and polyvinyl alcohol, and heating and stirring; (2) adding sodium carboxymethyl cellulose and continuing stirring to obtain a mixed solution; (3) After cooling to room temperature, the mixed solution is injected into a mold with a syringe, freeze-thawed, freeze-dried, and then immersed in a CaCl2 solution, cross-linked, rinsed multiple times, and freeze-dried again to obtain a attapulgite composite cellulose hydrogel material.

2. The method for preparing the attapulgite composite cellulose hydrogel material according to claim 1, characterized in that: The preparation method of the acid-modified attapulgite described in step (1) comprises the following specific steps: taking attapulgite, adding 1-5 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:4, stirring at 50-90°C for 1 hour, filtering, washing with distilled water until the filtrate is neutral, and drying to obtain acid-modified attapulgite.

3. The method for preparing the attapulgite composite cellulose hydrogel material according to claim 1, characterized in that: The mass ratio of the acid-modified attapulgite, sodium alginate, polyvinyl alcohol and sodium carboxymethyl cellulose is 0.5-1.5:1:0.5-1.5:0.5-1.

5.

4. The method for preparing the attapulgite composite cellulose hydrogel material according to claim 1, characterized in that: The heating and stirring temperature in step (1) is 80° C. and the time is 3-6 hours.

5. The method for preparing the attapulgite composite cellulose hydrogel material according to claim 1, characterized in that: The stirring time in step (2) is 5-8h.

6. The method for preparing the attapulgite composite cellulose hydrogel material according to claim 1, characterized in that: The specific steps of freeze-thaw in step (3) are: placing the mold at -20°C for freezing treatment for 16-20 hours, thawing at room temperature for 4-8 hours, and freezing and thawing for 2-3 cycles.

7. The method for preparing the attapulgite composite cellulose hydrogel material according to claim 1, characterized in that: The freeze-drying time in step (3) is 24 hours.

8. The method for preparing the attapulgite composite cellulose hydrogel material according to claim 1, characterized in that: The cross-linking time in step (3) is 3-12 hours.

9. The method for preparing the attapulgite composite cellulose hydrogel material according to claim 1, characterized in that: The concentration of the CaCl2 solution in step (3) is 3-6wt%.

Citation Information

Patent Citations

  • Modified attapulgite / sodium alginate / polyvinyl alcohol composite adsorbent as well as preparation method and application thereof

    CN112275264A

  • Preparation method of attapulgite-based adsorbent and application of attapulgite-based adsorbent in dye / heavy metal ion wastewater treatment

    CN114632501A

Cited By

  • Polysaccharide-based hydrogel adsorbent as well as preparation method and application thereof

    CN121372370A